an Introduction to Architectural Education - Hadi Nadimi (صفه)
The architectural body of our country, Iran , is at the moment passing through a period known as" The Crisis of Identity" Therefore it is the task of all experts to use their energy in the swift passage of this period to reach an era of cultural and self identity. In such circumstances architectural education requires more thorough and careful attention . This is due to the fact that the future of architecture is at stake. The future is in the hands of a younger generation of architects who with the acute training of their creative minds and upon relying on their cultural and moral beliefs , fundamental desiers and rich architectural inheritance draw up a clear path for the future of architectural design .The main concept of this article which has visualized architectural education by glancing at its present condition and its related models is the presentation of a number of propositions in the activation of the creative mind of the students as a liner aim in architectural studies and education